Identification of Novel Compound Heterozygous Variants of the PNPLA6 Gene in Boucher–Neuhäuser Syndrome - He, Junyu; Liu, Xin; Liu, Liyi; Zeng, Shaohao; Shan, Shuanghong; Liao, Zhihong (Frontiers in Genetics, 2022)
Background: Boucher-Neuhäuser syndrome (BNS, MIM 215470) is a rare autosomal recessive syndrome caused by mutations in the PNPLA6 gene. Few BNS cases have been reported for functional validation at the RNA level. Here, we report on the family of a 17-year-old girl with clinical characteristics of BNS, genetic validation, and a systematic review of PNPLA6 variants related to BNS. Methods: Clinical data and blood samples were collected from the patient and their parents, and whole-exome sequencing was performed and confirmed by Sanger sequencing. RNA sequencing and quantitative RT-PCR (qRT-PCR) were performed, and the three-dimensional protein structures of the variants were predicted. Results: We report a 17-year-old female with progressive night blindness since the age of four, primary amenorrhea, and non-development of secondary sexual characteristics. Her impaired vision was diagnosed as retinal pigmentary degeneration of the retina. She had congenital hypogonadotropic hypogonadism (CHH) but no cerebellar ataxia at present. Two novel compound heterozygous variants (c.2241del/p.Met748TrpfsTer65 and c.2986A>G/p.Thr996Ala) of the PNPLA6 gene (NM_006702.4) were identified by whole-exome sequencing. The former variant was carried from her healthy father and has not been reported previously. The latter was inherited from her healthy mother and was noted in a report without functional studies. The RT-PCR results showed that the mRNA expression of PNPLA6 was lower in this patient and her father than in the control group. She was diagnosed with BNS. Both variants (c.2241del and c.2986A>G) were likely pathogenic according to the ACMG criteria. The novel variants in the PNPLA6 gene related to Boucher-Neuhäuser syndrome were summarized in this article. Conclusion: The possibility of Boucher-Neuhäuser syndrome should be considered when patients present with night blindness, impaired vision, and hypogonadotropic hypogonadism. Gene sequencing is currently the primary diagnostic method. Here, novel compound heterozygous variants of PNPLA6 were identified in a BNS patient and verified its function at the RNA level. The PNPLA6 c.2241del variant is novel and potentially pathogenic, expanding the mutation spectrum in PNPLA6.